COFFEE PRODUCTION AND TRADE ANALYSIS IN NIGERIA: CURRENT STATUS, CHALLENGES AND OPPORTUNITIES - Babatunde, Olaitan Paul; Adesanya, Kehinde Ademola; Odey, Chinyere Florence; Balogun, Shamsudeen Tomiwa; Ebunola, Tope Emmanuel; Areola, Oluwatobi James (Socio-Economics/Agribusiness Department, 2026)
Coffee, a cornerstone of global agricultural trade, has seen a marked decline in Nigeria’s production and export sectors. This study examines coffee production and economic trade dynamics in Nigeria from 2000 to 2023, focusing on Coffea canephora (Robusta), Coffea arabica, and Coffea liberica. Utilizing the FAO data, the study employ Autoregressive Integrated Moving Average (ARIMA), Vector Autoregression (VAR), Vector Error Correction Model (VECM), and Johansen Cointegration models to analyze trends and relationships. The study revealed that production decreased from 3,830 tonnes in 2000 to 1,844 tonnes in 2023, driven by a 56% reduction in cultivated area. Exports are volatile, dropping from 1,699 tonnes (2006) to 21.73 tonnes (2023), with Nigeria’s global share at 0.000083%. Econometric results reveal a long-run equilibrium between production and exports, with global prices significantly influencing local markets. Key challenges include land scarcity, climate variability, limited market access, and price volatility, while opportunities lie in premium branding, land expansion, and policy reforms. Strategic interventions could reposition Nigeria in the global coffee economy, boosting rural livelihoods and foreign exchange earnings.